Measurement of associated production of a W boson and a charm quark in proton–proton collisions at √s=13Te - KAYA, MİTHAT (My University, 2019)
© 2019, CERN for the benefit of the CMS collaboration. Measurements are presented of associated production of a W boson and a charm quark (W + c) in proton–proton collisions at a center-of-mass energy of 13Te. The data correspond to an integrated luminosity of 35.7fb-1 collected by the CMS experiment at the CERN LHC. The W bosons are identified by their decay into a muon and a neutrino. The charm quarks are tagged via the full reconstruction of D ∗ (2010) ± mesons that decay via D ∗ (2010) ± → D + π ± → K ∓ + π ± + π ± . A cross section is measured in the fiducial region defined by the muon transverse momentum pTμ>26Ge, muon pseudorapidity | η μ | 5Ge. The inclusive cross section for this kinematic range is σ(W+c)=1026±31(stat)+76-72(syst) pb. The cross section is also measured differentially as a function of the pseudorapidity of the muon from the W boson decay. These measurements are compared with theoretical predictions and are used to probe the strange quark content of the proton.
Keywords: Fizik; Astronomi ve Astrofizik; Temel Bilimler; Mühendislik ve Teknoloji; Physics; Astronomy and Astrophysics; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; Uzay bilimi; ASTRONOMİ VE ASTROFİZİK; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; SPACE SCIENCE; ASTRONOMY & ASTROPHYSICS; Mühendislik (çeşitli); Fizik Bilimleri; Fizik ve Astronomi (çeşitli); Engineering (miscellaneous); Physical Sciences; Physics and Astronomy (miscellaneous)